HYDRODYNAMICS MODELING IN KENDARI BAY, SOUTHEAST SULAWESI, INDONESIA - Imalpen, Imalpen; Prartono, Tri; Rastina, Rastina; Koropitan, Alan Frendy; Yuliardi, Amir Yarkhasy (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2024)
Kendari Bay is coastal water in the center of the capital city of Southeast Sulawesi province. It is shaped like a pocket with a narrow mouth and there is an estuary of a large river, namely the Wanggu river, which makes the dynamics of its waters very interesting to study. The focus of the study is the hydrodynamic factors in the Kendari Bay and Wanggu River areas. This study aims to examine the hydrodynamic conditions of Kendari Bay, mainly due to the existence of reclamation and the influence of the Wanggu River which has not been studied previously. This research method uses a two-dimensional model based on bathymetric data, tides, and the flow of the Wanggu River with a simulation time of 15 days (1 March to 15 March 2020). The modeling results were then verified with PUSHIDROSAL tidal elevation data showing an RMSE value of 0.07 indicating that the model was well constructed. The mixed tidal type with a tendency to double daily is the tidal type of Kendari Bay waters based on the Formzahl number value of 0.51. The current pattern generally moves in and out from east to west and vice versa with a varying elevation range following spring conditions of 1.75 m. The maximum tidal speed is 0.1784 m/s and the minimum value is 0.0057 m/s which is shown in the sample results of the model when the hing to low tide, and low to high tide. The results of the hydrodynamic modeling show that the current velocity increases when passing through a narrow path, namely the bay estuary and river estuary. The existence of the reclamation area affects the changes in the velocity of the current which is significantly larger and the direction of the current that undergoes a deflection follows the shape of the reclamation area. The current direction is to the southeast and then turns towards the northeast when low to high tide and eastward then turns towards the northeast when the high to low tide spring conditions compared to research before the reclamation